The Mediating Role of Knowledge Management in the Impact of Information Technology Infrastructure on Learning and Training Optimization - Bahrami, Masoumeh; Molayi, Sahel (Digital Transformation and Administration Innovation, 2025)
The present study aims to investigate the mediating role of knowledge management in the impact of information technology infrastructure on the optimization of learning and training. In terms of purpose, this study is applied, and in terms of method, it is descriptive-correlational. The statistical population consists of managers and entrepreneurs of knowledge-based companies in Isfahan, among whom 93 individuals were selected using Cochran's formula and a random sampling method. To collect the required data, a researcher-made questionnaire based on a five-point Likert scale was employed. The content validity of the instrument was confirmed by experts and specialists, and Cronbach’s alpha as well as composite reliability were used to assess the reliability. Upon distributing the questionnaire, the validity of the instrument was evaluated through three methods: construct validity (outer model), convergent validity (AVE), and discriminant validity. The AVE value for all variables should be greater than 0.50. To test the research hypotheses, structural equation modeling was conducted using SmartPLS 2 statistical software. The findings of the study indicate that all research hypotheses were supported. Accordingly, information generation, information networking, and provision of technical knowledge have a significant impact on knowledge management. Furthermore, knowledge management demonstrated a significant impact on the optimization of learning and training.